Cloud Computing Environments for Biomedical Data Services - Penhaker, Marek; Krejcar, Ondrej; Kasik, Vladimir; Snášel, Václav (Intelligent Data Engineering and Automated Learning - IDEAL 2012, 2012)
The goal of the project we describe in this paper was the cloud computer environment establishment for biomedical data processing services using a security access. The relevant cloud application for user interactive interaction with biomedical data were realized on .NET Framework technology platform by the help of rapid calculating by FPGA technology. Interconnection of these technologies allows a large spectrum of users to quick access to pre-evaluated biomedical data. This article discusses the possible topological solutions and implementation of that system.